Colonization of nasal cavities by Staphylococcus epidermidis mitigates SARS‐CoV‐2 nucleocapsid phosphoprotein‐induced interleukin (IL)‐6 in the lung. Issue 7 (14th April 2022) - Kao, Ming‐Shan; Yang, Jen‐Ho; Balasubramaniam, Arun; Traisaeng, Supitchaya; Jackson Yang, Albert; Yang, John Jackson; Salamon, Benjamin Prethiviraj; Herr, Deron R.; Huang, Chun‐Ming
Summary: Infection by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) can trigger excessive interleukin (IL)‐6 signalling, leading to a myriad of biological effects including a cytokine storm that contributes to multiple organ failure in severe coronavirus disease 2019 (COVID‐19). Using a mouse model, we demonstrated that nasal inoculation of nucleocapsid phosphoprotein (NPP) of SARS‐CoV‐2 increased IL‐6 content in bronchoalveolar lavage fluid (BALF). Nasal administration of liquid coco‐caprylate/caprate (LCC) onto Staphylococcus epidermidis ( S. epidermidis )‐colonized mice significantly attenuated NPP‐induced IL‐6. Furthermore, S. epidermidis‐ mediated LCC fermentation to generate electricity and butyric acid that promoted bacterial colonization and activated free fatty acid receptor 2 (Ffar2) respectively. Inhibition of Ffar2 impeded the effect of S. epidermidis plus LCC on the reduction of NPP‐induced IL‐6. Collectively, these results suggest that nasal S. epidermidis is part of the first line of defence in ameliorating a cytokine storm induced by airway infection of SARS‐CoV‐2. Abstract : Nasal administration of liquid coco‐caprylate/caprate (LCC) onto Staphylococcus epidermidis (S. epidermidis)‐colonized mice significantly attenuated NPP‐induced IL‐6. Inhibition of Ffar2 impeded the effect of S. epidermidis plus LCC on the reduction of NPP‐induced IL‐6. Collectively, these results suggest that nasal S. epidermidis is part of the first line of defense in ameliorating a cytokine storm induced by airway infection of SARS‐CoV‐2.